Effects of exendin‐4 on colonic motility in rats and its underlying mechanism. Issue 2 (10th October 2018) - Yan, Lin; Tang, Qincai; Quan, Xiaojing; Ren, Haixia; Chen, Wei; Xia, Hong; Luo, Hesheng
Abstract: Background: Glucagon‐like peptide‐1 (GLP‐1) receptor (GLP‐1R) agonists modulate gastrointestinal motility; however, the effects of GLP‐1R agonists on colonic motility are still controversial, and the molecular mechanism is unclear. Exendin‐4 shares 53% homology with GLP‐1 and is a full agonist of GLP‐1R. In this study, our aims were to explore the role and mechanism of exendin‐4 in isolated rat colonic tissues and cells. Methods: An organ bath system was used to examine the spontaneous contractions of smooth muscle strips. The whole‐cell patch‐clamp technique was used to investigate the currents of L‐type voltage‐dependent calcium channels and large conductance Ca 2+ ‐activated K + (BKCa ) channels in smooth muscle cells. Key Results: Exendin‐4 decreased both the amplitude and frequency of spontaneous contractions of smooth muscle strips in a concentration‐dependent manner. The inhibitory effect was completely blocked by exendin‐4(9‐39), a GLP‐1R antagonist. Moreover, this effect was partially abolished by tetrodotoxin (TTX), a blocker of neuronal voltage‐dependent Na + channels, Nω‐Nitro‐l ‐arginine (L‐NNA), a nitric oxide synthase (NOS) inhibitor, apamin, an inhibitor of small‐conductance Ca 2+ ‐activated K + (SK) channels. Whole‐cell patch‐clamp recordings revealed that exendin‐4 inhibited the peak current of L‐type calcium channels in colonic smooth muscle cells, but did not change the shape of the current‐voltage (I‐V) curves. The steady‐state activation and steady‐state inactivation of L‐type calcium channels were not affected. Likewise, BKCa currents were significantly inhibited by exendin‐4. Conclusions: Exendin‐4 indirectly inhibits colonic muscle activity via a nitrergic and a purinergic neural pathway through NO and ATP release and inhibits L‐type voltage‐dependent calcium channels and BKCa channels in smooth muscle cells. Abstract : Exendin‐4 indirectly inhibits colonic muscle activity via a nitrergic and a purinergic neural pathway through NO and ATP release and inhibits L‐type voltage‐dependent calcium channels and BKCa channels in smooth muscle cells.